2008
DOI: 10.1186/1471-2407-8-240
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an in vivo model of canine prostate carcinoma using the new cell line CT1258

Abstract: Background: Prostate cancer is a frequent finding in man. In dogs, malignant disease of the prostate is also of clinical relevance, although it is a less common diagnosis. Even though there are numerous differences in origin and development of the disease, man and dog share many similarities in the pathological presentation. For this reason, the dog might be a useful animal model for prostate malignancies in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
4
30
0
6
Order By: Relevance
“…Consistent with observations by Fork et al [14] no animal developed metastases which might have been caused by fast tumour progression leading to euthanasia of the animal. Moreover, there seems to be a low disposition of CT1258 cells to metastasise as the primary tumour was obtained from a 10 year old dog which -despite of several small metastases in the mesentery – showed no signs of abnormalities [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with observations by Fork et al [14] no animal developed metastases which might have been caused by fast tumour progression leading to euthanasia of the animal. Moreover, there seems to be a low disposition of CT1258 cells to metastasise as the primary tumour was obtained from a 10 year old dog which -despite of several small metastases in the mesentery – showed no signs of abnormalities [13].…”
Section: Discussionsupporting
confidence: 92%
“…In conventional in vivo studies characterising tumour development in rodent models as the study by Fork et al, the tumour development was analysed via manual palpation whereby the tumours were allowed to grow to a size ranging from 5 to 8 mm which lasted 20 to 42 days after s.c. injection of CT1258 cells [14]. In the present study, the two animals inoculated with unlabeled cells showed comparable results to the Fork study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In perspective, this could allow to characterise if abundantly expressed recombinant HMGA2 can increase the highly tumourigenic potential of CT1258 which was previously demonstrated in a murine NOD/SCID in vivo model [46], [47]. The first characterisation of this hypothesis needs to be carried out carefully in an intermediary in vivo mouse model.…”
Section: Discussionmentioning
confidence: 96%
“…Subcutaneous (s.c.) injection, which has been widely used in the development of most human tumor models (4,5), was also considered as the most appropriate method for lung cancer in our study, because orthotopic implantation is prone to complications, and its rate of tumorigenicity and metastasis formation in vivo is always unstable (6). Furthermore, unlike breast cancer and melanoma, an orthotopic model for lung cancer is relatively unavailable due to the inaccessibility of the anatomical location.…”
Section: Introductionmentioning
confidence: 99%